(untitled) (University Journal of Zoology, Rajshahi University, 2009)
This study has been conducted in four Districts (i.e., Nadia, North 24-Parganas, Hooghly and Burdwan) of the Gangetic plain of West Bengal, India. The results of the present study indicate that these Districts are badly infested by various types of rodents. Among them wild Indian house rat (Rattus rattus) is quite preponderant followed by field mice (Mus musculus), Norway rat (Rattus norvegicus) and Indian mole rat (Bandicota sp). Percentage of the female individual of these species is higher than the male individual. They cause severe types of damages in the fields and houses. In the District Nadia, Hooghly, North 24-Parganas and Burdwan, paddy and potato were damaged and estimated during the study period. Other crops and vegetables such as wheat, gourd, cauliflower, cabbage and jute were also damaged by the rodents. Household properties e.g., books, clothes, utensils and electronic goods were also destroyed by the rats. Damages were maximum in the mud built houses. They build their nest and burrows in the upland, trees and periphery of the field but extensive damages were noticed in the centre of the field. Rodents breed throughout the year but peak breeding seasons are August to October and late winter season and average litter size is about 6 to 8. The present study also points out the migratory behavior, hoarding materials in the burrows, nature of damages in relation to field conditions. For the control operation of the rodents and especially the rats, it is essential to have a clear-cut idea about the species present in the area, their habit and habitat, mode of burrowing, their movements, preference of food and a detailed life history of predominant rodent species. These aspects have been thoroughly studied in the present investigation. Key words: Gangetic plain, West Bengal, rodents, Rattus rattus, paddy, burrow. Â Â doi:10.3329/ujzru.v27i0.1961 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 85-90